Essaouira, “The Wind City” as a “Cultural Product” - Bauer, Susanne; Escher, Anton; Knieper, Sebastian (ERDKUNDE, 2006)
The following paper discusses the genesis of a town and its marketing as a “cultural product” (Scott 1997) to international tourists, taking the Moroccan coastal town Essaouira as an example. First, we will explain the theoretical concept of cultural product in the context of economic globalization, self-fashioned individualization and European gentrification. A brief outline of the history of the once flourishing port town of Essaouira illustrates the current peripheral and marginal situation of this town in 20th century Morocco. After that, we will describe the local cultural goods. An important group of consumers are the Europeans who moved to the old town during the last few decades. It can be shown that the cultural goods of Essaouira act as a backdrop and stage for these Europeans, and the variables “atmosphere and creativity” and “individual self-realization and social acceptance” that are referred to below as “post-modern goods” serve as reason and motivation, inspiring them to select Essaouira’s old town as their home. In this case, emphasis is placed on the freedom the Europeans there enjoy in being able to live opposing aspects of individualism and social acceptance. As a result, Essaouira may be called for the European new Souiris a “place on the margin” as described by Shields (1991) where Europeans are subject to other rules and norms than in the heart of Europe. It is to be hoped that future urban and regional planning will preserve Essaouira’s cultural goods and not sacrifice them during planning discussions in favour of mass tourism (Plan Azur 2003).